(untitled) (Journal of Pharmaceutical Negative Results, 2023)
In this article, the adjective word group in the Uzbek language and its linguistic nature were treated, and the reasons for the meaning transfer of adjective lexemes were studied and explained. Also, the phenomenon of conversion observed in adjectives was highlighted, the semantic-functional features of adjectives in the Uzbek language were revealed, and their possibilities in the text were explained.